Вы находитесь на странице: 1из 11

.

2 .

1-4. ()
y = f ( x) () x0 , O ( x ) \ x0 : x < x0 : f ( x ) < f ( x0 )(>)
x > x0 : f ( x ) > f ( x0 )(<) .
y = f ( x) () X , x1 , x2 X : x1 > x2 : f ( x1 ) > f ( x2 )(<) .
5-6. ()
y = f ( x) () X , y = f ( x) ( )
X .
x0 X x X f ( x) () f '( x0 )( x x0 ) + f ( x0 )
7.
x0 , x0
.
8.
y = f ( x) c f (2) (c ) = 0 . ,
f (2) ( x) c ,
M (c, f (c)) .
y = f ( x) c
f (2) (c ) = 0 , f (3) 0 , M (c, f (c)) .
n 2 y = f ( x) n
c n + 1 c .
f (2) (c ) = ... = f ( n) (c) = 0, f ( n +1) (c ) 0 ,
M (c, f (c)) .
9.
x0 - y = f ( x) , x0 -
.
10-11. ()
y = f ( x) x0 (),
O ( x0 ) : x O ( x0 ) \ x0 : f ( x ) < f ( x0 )(>) .
12.
y = f ( x) - x0 , x0 - f '( x0 ) = 0
13.

y = f ( x) - , x0 - ,
f '( x ) .
y = f ( x) - , f '( x0 ) = 0 f ''( x0 ) > 0(<) x0
()
n 1 y = f ( x) n
c n + 1 c .
f (2) (c ) = ... = f ( n) (c) = 0, f ( n +1) (c ) 0 ,
c , f ( n +1) (c) < 0 , f ( n +1) (c) > 0 .
14.
y = f ( x) [a, b] ,
I d {xk }
.
I y = f ( x) a b
b

f ( x)dx .
a

15.
n

S n = M k xk , M k = max f ( x)
i =1

[ xk 1 , xk ]

sn = mk xk , M k = min f ( x )
i =1

[ xk 1 , xk ]

16.
y = f ( x) I * ,
{S } y = f ( x) [a, b] .
y = f ( x) I* ,
{s} y = f ( x) [a, b] .
17.
[a, b] y = f ( x)
*
, I* = I .
[a, b] y = f ( x)
, > 0 {xk } [a, b] , S s < .
18.
[a, b] .
[a, b] .
y = f ( x) [a, b] . > 0
, y = f ( x)
[a, b]

19. -.
y = f ( x) [a, b]
b

f ( x)dx = F (b) F (a) , F ( x) -

y = f ( x) [a, b] .

20.
y = f ( x) y = g ( x) [a, b] ,
b

f ( x) g '( x)dx = f ( x ) g ( x) |ba f '( x) g ( x)dx .


a

21.
x = g (t ) [m, M ] min t[ m , M ] g (t ) = a , max t[ m ,M ] g (t ) = b ,
g (m) = a, g ( M ) = b .
b

f ( x)dx = f [ g (t )]g '(t )dt ( ,

y = f ( x) )

22.
b

1
M[ f ] =
f ( x)dx y = f ( x) [a, b] .
a b a
23.
b

y = f ( x) [a, b] , c (a, b) : M [ f ] =

1
f ( x)dx = f (c) .
a b a

24.
f ( x) -
g ( x) 0
[m, M ] m = inf[ m , M ] f ( x) , M = sup[ m , M ] f ( x) ,
b

f ( x)dx = g ( x)dx
25.
f ( x), g ( x) -
g ( x) -
b

[a, b] : f ( x) g ( x)dx = g (a ) f ( x)dx + g (b) f ( x)dx


26. .
A

F ( A) = lim f ( x)dx , ,
Alim
+
A+
a

y = f ( x) [a, +)

f ( x)dx , ,

f ( x)dx

27.

f ( x)dx = lim

A+

f ( x)dx .
a

lim
+0

f ( x)dx , ,

y = f ( x) [a, b]

f ( x)dx
a

f ( x)dx

f ( x)dx = lim

+0

28.
,
R ''

f ( x)dx |< .

> 0 A( ) > a : R ', R '' > A : |

R'

29.
,
> 0 A( ) > a : R ', R '' > A : |

R ''

f ( x)dx |> .

R'

30.
,
> 0 ( ) > 0 : ', '' : 0 < '' < ' < : |

b ''

f ( x )dx |< .

a '

31.
,
> 0 ( ) > 0 : ', '' : 0 < '' < ' < : |

b ''

f ( x)dx |> .

a '
+

32.

sin x
dx
x

1 < p < 2
0 < p 1 .
+

33.

p > 1
0 < p 1 .
+

34.

p x

e dx

< 0

= 0 .
p < 1
35.

x
0

p x

e dx

sin x
dx
x

f ( x) dx .

< 0

p > 0

.
= 0

p = 0

36. v. p. f ( x)dx

y = f ( x) (, +)
. , y = f ( x) ,
A

lim

A+

f ( x)dx = v. p. f ( x)dx,

.
b

37. v. p. f ( x)dx
a

y = f ( x) [a, b] , c , a < c < b ,


[a, c) , (c, b] . , y = f ( x) ,

c

lim (

+0

f ( x)dx +

f ( x )dx) = v. p. f ( x)dx, > 0

c +

.
38.
+

f ( x), g ( x) [a, +) x | f ( x) | g ( x) ,

g ( x)dx

f ( x)dx .

| f ( x) | dx g ( x)dx .

39.
f ( x), g ( x) lim
x
+

f ( x)
=k 0
g ( x)

g ( x)dx

f ( x) dx .

40.
0 < a x < + y = f ( x) | f ( x ) |

c
,c
x

, > 1 .

f ( x) dx .

c > 0 :

c
0 < a x < + f ( x ) , < 1 ,
x

f ( x)dx

.
41. -
1. y = f ( x) a x < +
F ( x)

2. g ( x) - a x < +
x
3. g '( x) a x < +
+

f ( x) g ( x) dx .

42.
+

| f ( x) | dx -

f ( x )dx - .

43.

| f ( x) | dx -,

f ( x) dx -

f ( x )dx .

44.
S y1 ( x ), y2 ( x ) ( y2 ( x) > y1 ( x )
x = a, x = b ( a < b )),
b

S = ( y2 y1 ) dx .
a

x = x(t ), y = y (t ) ( 0 t T )
C ,
S ,
T
T
T
1
S = ( y (t ) x '(t )dt = x(t ) y '(t )dt = ([ x (t ) y '(t ) x '(t ) y (t )]dt .
20
0
0
45. , ,
S OAB r = r ( )
= , = ( < ) ,
S=

1 2
r ( )d
2

46.
( )
x = x(t ), y = y ( x) (a x b)
b

S = 1 + y '2 ( x)dx
a

x = x(t ), y = y (t ) (t0 t T ) , x = x(t ), y = y (t )


[t0 , T ] ,
T

S = x '2 (t ) + y '2 (t )dt


t

47.
r = r ( ) ( ) , r = r ( ) [ , ] ,

S = r 2 ( ) + r '2 ( ) d .

48.
, AB OX ,
B

P = 2 | y | ds ,
A

ds
b

1)

y ( x) S = 2 1 + y x 'dx
a

t1

2)

x(t ), y (t ) S = 2 | y (t ) | x '2 + y '2 dt


t0

3) ( ) S = 2

| sin |

r '+ r2 d

49.
, OX
a x b, 0 y y ( x ) ,
y ( x) ,
b

Vx = y 2 ( x) dx .
a

50. n-
m
{M n } E ,
m
A E , > 0 N : n N ( M n , A) < .

A {M n } .
51. -
{M n } m -
.
52.

b u = f ( M ) A , A
{M n } {M } , M n

A , { f ( M n )}
b .

b u = f ( M ) A ,
> 0 ( , A) : 0 < ( M n , A) < | f ( M ) b |<
53.
b u = f ( M ) M ,
> 0 ( ) : M {M } : (O, M ) > | f ( M ) b |<
54-55. (
)
u = f ( M ) M = A ( M ),
, M = A ( M ) .
, M = A (
M ),

> 0 ( ) : M 1 , M 2 {M } : 0 < ( M1 , A) < , 0 < ( M2 , A) < ( ( M 1 , A) > , 0 < ( M 2 , A) > ):
| f ( M 1 ) f ( M 2 ) |< .

56.

u = f ( M )

A , A
{M n } {M } ,
{ f ( M n )} f ( A) .

u = f ( M ) A ,
> 0 ( , A) : ( M n , A) < | f ( M ) f ( A) |<

57.
u = f ( M ) {M n }
E m , > 0 ( ) : M ', M '' {M } : ( M ', M '') < | f ( M ') f ( M '') |< .
58.

.
60.
u = f ( M ) A A
m
E f ( A) 0 , - A ,
f ( M ) , f ( A) .

61.

u = f ( M ) {M }
E m , f ( A) f ( B ) - A B . , , C , f ( A) f ( B ) . L ,
A B {M } , N , , f ( N ) = C .
62.

u = f ( M ) {M } ,
.

u = f ( M ) {M } ,
.
63.

xk

xk u
xk

f ( x1 ,..., xk 1 , xk + xk , xk +1 ,..., xm ) f ( x1 ,..., xm )

xk

M ( x1 ,..., xm ) xk xk

xk 0 , u = f ( x1 ,..., xm ) M
u
xk
.
xk

x
u
= lim k
xk xk 0 xk

64.
u = f ( x1 ,..., xm ) M ( x1 ,..., xm ) ,

u = A1 x1 + ... + Am xm + 1 x1 + ... + m xm ,
A1 ,..., Am - x1 ,..., xm , 1 ,..., m
x1 0,...., xm 0 , x1 = x2 = .... = xm .
65.
du M ( x1 ,..., xm ) u = f ( x1 ,..., xm )
M .
u = A1 x1 + ... + Am xm + 1 x1 + ... + m xm
Ai
, du M
.
66.

(d n 1u ) (n 1) - d n 1u , xi = dxi , i = 1,..., m
n u = f ( x1 ,..., xm ) ( M ( x1 ,..., xm )
)
n
d u .
67.
x1 = 1 (t1 ,..., tk )

0
0
(*) . . . . .
M (t1 ,..., tk ) ,
x = (t ,..., t )
m 1
k
m
u = f ( x1 ,..., xm )

N ( x10 ,..., xm0 ) ,

xi0 = i ( t ,..., t ), i = 1,..., m. u = f ( x1 ,..., xm ) , x1 ,..., xm


0
1

0
k

(*) , M .
u u x1
u xm
=
+ ... +
, p = 1,..., k ,
M
t p x1 t p
xm t p

u
x
, q = 1,..., m N , i (*)
xq
t j

t1 ,..., tk M .
68.

n 0 , u = f ( x1 ,..., xm )

M 0 ( x1 ,..., xm ) n + 1 .
u = f ( M ) f ( M 0 ) M 0 :
1
1
1
u = du |M 0 + d 2 u |M 0 +... + d n u |M 0 +
d n +1 u |N ,
2!
n!
(n + 1)!
N - , , , M ( x1 ,..., xm ) ,
k
n +1
0
dxi xi d u |M 0 d u |N , xi = xi xi .

n 0 - , u = f ( M ) = f ( x1 ,..., xm ) n 1 0
0
0
0
M 0 ( x1 ,..., xm ) n M 0 ( x1 ,..., xm ) .

1
1
f ( M ) = f ( M 0 ) + du |M 0 + d 2 u |M 0 +... + d n u |M 0 +o( n )
2!
n!


( M 0 , M ) , o( n )
0 ( M M 0 ) , n .
69.

F (u , x1 , x2 ) M 0 (u , x1 , x2 )
F
M 0 . , M 0 F
R ,
u
F
,
,
u

M 0 '( x1 , x2 ) R ' ,
u = ( x1 , x2 ) ,
0

| u u |<
F (u , x1 , x2 ) = 0 ,
u = ( x1 , x2 ) M 0 ' .
72-73. ()
u = f ( M ) M 0 (),
O ( M 0 ) {M } : M O ( M 0 ) \ M 0 f ( M ) < f ( M 0 )(>) .
74.
u = f ( M ) M 0 ,
, .
75.
0
0
u = f ( M ) = f ( x1 ,..., xm ) M 0 ( x1 ,..., xm )
u
= 0, i = 1,..., m
x
,...,
x

x
1
m
i

,
.

76.
u = f ( M ) = f ( x1 ,..., xm )
M 0 ( x10 ,..., x 0m ) M 0 . M 0
m

(*) du |M 0 = aik dxi dxk


u = f (M )
du |M 0 = 0
i =1 k =1

, ..
.
,
2
u
aik = aki =
xi xk ()

dxi , i = 1,...m , u = f ( M ) M 0
(). (*)
, M 0 M 0
/